SURVIVAL OF Cronobacter sakazakii IN SKIM MILK DURING SPRAY DRYING, STORAGE AND RECONSTITUTION [Ketahanan Hidup Cronobacter sakazakii dalam Susu Skim selama Proses Pengeringan Semprot, Penyimpanan dan Rekonstitusi] - Ratih Dewanti Hariyadi; Fenny Larasati; Lilis Nuraida (Jurnal Teknologi dan Industri Pangan, 2012)
Cronobacter sakazakii is an emerging pathogen known to survive dry conditions and its presence in powder infant formula (PIF) has been linked to several outbreaks. In Indonesia, isolation of this bacterium from various foods have been reported. The objective of this study was to determine the effect of spray drying and storage humidity on the survival of C. sakazakii YRc3a in skim milk and their viability upon reconstitution. The survival of Cronobacter during spray drying was determined by comparing the number of bacteria before and after drying. The viability of Cronobacter in spray dried skim milk (SDSM) during storage was observed at weeks 1 to 8 and 12. At the same intervals, SDSM containing the pathogens was reconstituted at either 27°C or 50°C and the survivors were enumerated. The data were plotted to yield survival curves. Spray drying caused 4.19 log CFU/g reduction of Cronobacter and the bacteria experiencing drying were less sensitive to reconstitution at 50°C. During storage, the water activity of SDSM reached equilibrium at week 2 and afterwards, they started to decrease when stored at 50% or 90% RH, but maintained its viability at 70% RH. Storage at 50% and 90% RH accelerated the death rate of C. sakazakii YRc3a, resulting in the decline of the viable counts for 3 log cycles. At 50% RH, C. sakazakii Yrc3a decreased significantly, but the survivors exhibited increased heat resistance with the lowest reduction upon reconstitution at 50°C (0.16 log CFU/ml).